Pembuatan Program Absensi Sidik Jari untuk Bagian Pergudangan PT. Puji Surya Indah - Hans Sebastian Thenady; Alexander Setiawan; Agustinus Noertjahyana (Jurnal Infra, 2019)
Employee’s productivity could affect the performance of a company, so it must be considered & maintained. One way to maintain the employee’s productivity is by monitoring the employee’s performance through their attendance. But, it also requires the right tool to prevent the forgery of attendance data input by employees. For example, if you use a timestamp machine, the company’s employees can fake data on their absences by entrusting the attendance card (to be stamped) to their colleagues. Therefore, an attendance program that is assisted by using a fingerprint machine, will be designed to help the company maintain the productivity of the employees of the Puji Surya Indah company. This attendance program consists of a user interface, which will be created using Visual Studio 2017, with the Visual Basic programming language. In addition, a database was also established to store employee, user, and attendance and payroll data, using MySQL. The final result of making this program is an attendance program, which can store personal data of employees, user data, along with attendance reports and employee’s salaries. The conclusion obtained from the making of this program is that this program is feasible to use, but still needs to be added features and justify the way the data is displayed; overall, this program gets scores of 66.6% good and 3.33% adequate from respondents.